Bowel function and quality of life following surgery for deep endometriosis. (3rd July 2022) - Scheepers, Wessel F. W.; Maas, Jacques W. M.; van de Kar, Majorie M. A.
Abstract: Objective: To assess the influence of surgical approach, complications and patient characteristics and their postoperative functional outcomes on (sexual) quality of life (QoL) in patients with deep endometriosis (DE) with bowel involvement. Methods: Retrospective cohort study on patients surgically treated for DE in a Dutch tertiary referral hospital. Data are based on surgical records and questionnaires covering current postoperative bowel function and (sexual) QoL. Results: Postoperative functional score outcomes: constipation, fecal incontinence and Low Anterior Resection Syndrome (LARS) did not differ between patients treated with rectal shaving or segmental resection. Thirty percent of women treated with rectal shaving experienced LARS-like symptoms as well. Women who underwent segmental resection had a worse sexual QoL compared to patients managed by shaving. Patients who suffered from complications had a worse postoperative QoL. A higher postoperative constipation score was correlated with a significantly higher pain score and a lower overall and sexual QoL. LARS-score was correlated with a worsened sexual QoL. Conclusion: Women who underwent surgery for deep endometriosis rated their overall QoL as lower when a complication occurred. Segmental resection resulted in a lower sexual QoL compared to shaving. We showed that a higher LARS-score correlates with a lower sexual QOL, and postoperative constipation with more pain and a lower overall and sexual QoL. Interestingly, after using the shaving technique one-third of the patients experienced LARS-like symptoms as well.